Tautology in the Resource-Based View and the Implications of Externally Determined Resource Value: Further Comments - Priem, Richard L.; Butler, John E. (Academy of Management Review, 2001)
Richard L. Priem, John E. Butler, Tautology in the Resource-Based View and the Implications of Externally Determined Resource Value: Further Comments, The Academy of Management Review, Vol. 26, No. 1 (Jan., 2001), pp. 57-66